The level of challenges facing educational digital games in Jordanian private schools from the perspective of educators working there - Al-Baher, Ibrahim; Alalawi, Lamia (Technium Social Sciences Journal, 2025)
The study aimed to identify the level of challenges facing educational digital games in Jordanian private schools from the perspective of educators working there, the study sample, which was stratified randomly, consisted of (382) educators. The descriptive survey approach was used in the current study. To achieve the objectives of the study, a questionnaire was developed, and its validity and reliability were verified. The results showed that the level of challenges facing educational digital games in Jordanian private schools from the point of view of educators working in Jordanian private universities was moderate. The results of the study also showed the presence of statistically significant differences at the significance level (α≤ 0.05) according to the gender variable in favor of the male category, and the absence of statistically significant differences according to the Years of experience variable, and the absence of statistically significant differences according to the academic rank variable. In light of these results, the study recommended that private schools give educational digital games great importance so that they work to stimulate conducting studies and research from time to time to study the challenges facing educational digital games and master them and try to reach a way to reduce their impact.